Cyberdelics in context: On the prospects and challenges of mind-manifesting technologies - Hartogsohn, Ido (Frontiers in Psychology, 2023)
The concept of cyberdelics emerged in the 1980s as an umbrella term denoting the nexus connecting cybernetic (digital) technologies and psychedelic (mind manifesting) drugs. Cyberdelic technologies, in particular the then emerging field of virtual reality, were touted by psychedelic cultural icons including Timothy Leary and Terence McKenna as auguring a new era of digital mind-expansion where psychedelic experiences will be recreated online inside virtual worlds. Cyberdelic culture waned in the 2000s. However, recent years have seen the return of the cyberdelic imaginary, following on the heels of a psychedelic resurgence and a renewed interest in virtual reality technologies and their use in therapy. Cyberdelic advocates speak of the necessity of creating transformative technologies that steer humanity away from mindless consumerism and distractedness, and towards expanded states of awe, presence, and transcendence. Nevertheless, much like psychedelics, cyberdelic technologies are seen as running against the grain of current sociocultural arrangements and economic models which threaten to quell their transformative potential. Research on psychedelics within the humanities over the past decade has emphasized the role of cultural set and setting: the significance of the cultural embeddedness of these psychoactive agents and the dependence of their effects on surrounding sociocultural conditions. Building on the notion of information technologies as mind-manifesting technologies, this paper sets out to consider what psychedelics can teach us about cyberdelics: how the principles of set and setting and current discussions within the psychedelic humanities can inform our understanding of the resurgence of interest in cyberdelic media, its prospects, and challenges.